Caracterização molecular do vírus da hepatite B em pacientes cronicamente infectados em um centro de referência em Goiânia-GO - Santos, Norrama Araújo (2019)
Genotypes of hepatitis B virus and the occurrence of mutations in the genome may interfere with treatment response, disease progression to chronic form, cirrhosis and hepatocellular carcinoma. The objective of the present study was to analyze the molecular characteristics of HBV in patients with chronic hepatitis B in Goiânia-Goiás. Blood samples (N = 53) were collected from patients who were attended / followed at a referral hospital in Goiânia-Goiás. Initially, an interview was conducted with structured questionnaire on sociodemographic data, possible characteristics associated with the risk of HBV acquisition and previous vaccination against hepatitis B. Other information, such as clinical data, use of antiviral therapy and results of complementary tests were collected in the medical record and with the doctor in charge. All samples were screened for HBV serological markers (HBsAg, Anti-HBc, Anti-HBs, HBeAg and Anti-HBe) using commercial kits. Subsequently, viral DNA extraction and a semi- nested PCR were performed using primers complementary to the Pre-S / S (PS1, S2 / S22 and SR) and Pre-C / C (X1, C2, X4 and C3) regions of HBV. Then the samples were sequenced to the S and PreC / C regions of HBV for the determination of genotypes / subgenotypes and mutation screening. The nucleotide sequencing was performed in 22 samples, and the genotypes / subgenotypes A1 (n = 09), A2 (n = 01), D2 (n = 02), D3 (n = 07), and F2 were found. Mutations in the Pre C / C region (S171T, G1764A), region S (S45T, P46T, T114S, K122T, T123T, T143S, A159G, Y161F, I213L, L21S, T118A, V47G, P127L, F183C, M198I. Y206C, R24K, S61L, F8S, T127P, I68T, Y100C) and P region (I91L, Y126H, W153R, Y126R, V207L, L129M, Q130P) were identified and previously described in the literature, in patients with chronic hepatitis B. Furthermore, the presence of some nucleotide substitutions in the S regions (V47G, L42C, L14S, V14C, L15Y, Q16R, A17R, G44A, L49P, H61L, F158L, P178Q, F19C, I4L, T5H, G22D, G18C, F19V) and also in P (E11Q, H13Y, H13T, I16T, P17L, R18G, T19P, P20L, A21L, R22V, V23L, T24Q, G25A, G26V, V27F, L29F, A38T, R110G, H122F, M124H, L129M, I135N, S135Y, S137T, Q139N, M145L, Y148F, K149F, Y148F, Y151L) which have not been described in previous studies. The results of the present investigation confirm the predominance of circulation of A/D/F genotypes in Brazil and in our Region. In addition, they confirm the presence of mutations in the HBV genome in treatment-naive patients or under the use of antiviral therapy. Therefore, these data contribute to knowledge regarding chronic HBV infection and reinforce the importance of molecular monitoring in infected patients.